Molecular mechanisms of serotonergic action of the HIV-1 antiretroviral efavirenz. (August 2016) - Dalwadi, Dhwanil A.; Kim, Seongcheol; Amdani, Shahnawaz M.; Chen, Zhenglan; Huang, Ren-Qi; Schetz, John A.
Graphical abstract: Abstract: Efavirenz is highly effective at suppressing HIV-1, and the WHO guidelines list it as a component of the first-line antiretroviral (ARV) therapies for treatment-naïve patients. Though the pharmacological basis is unclear, efavirenz is commonly associated with a risk for neuropsychiatric adverse events (NPAEs) when taken at the prescribed dose. In many patients these NPAEs appear to subside after several weeks of treatment, though long-term studies show that in some patients the NPAEs persist. In a recent study focusing on the abuse potential of efavirenz, its receptor psychopharmacology was reported to include interactions with a number of established molecular targets for known drugs of abuse, and it displayed a prevailing behavioral profile in rodents resembling an LSD-like activity. In this report, we discovered interactions with additional serotonergic targets that may be associated with efavirenz-induced NPAEs. The most robust interactions were with 5-HT3A and 5-HT6 receptors, with more modest interactions noted for the 5-HT2B receptor and monoamine oxidase A. From a molecular mechanistic perspective, efavirenz acts as a 5-HT6 receptor inverse agonist of Gs -signaling, 5-HT2A and 5-HT2C antagonist of Gq -signaling, and a blocker of the 5-HT3A receptor currents. Efavirenz also completely or partially blocks agonist stimulation of the M1 and M3 muscarinic receptors, respectively. Schild analysis suggests that efavirenz competes for the same site on the 5-HT2A receptor as two known hallucinogenic partial agonists (±)-DOI and LSD. Prolonged exposure to efavirenz reduces 5-HT2A receptor density and responsiveness to 5-HT. Other ARVs such as zidovudine, nevirapine and emtricitabine did not share the same complex pharmacological profile as efavirenz, though some of them weakly interact with the 5-HT6 receptor or modestly block GABAA currents.